2016
DOI: 10.1071/cp15239
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of QTLs controlling multiple traits in sorghum

Abstract: Sweet sorghum (Sorghum bicolor L. Moench) is a promising crop for biofuel and forage production, having strong resilience to multiple stresses and being capable of thriving on marginal land. The main goals in sweet sorghum improvement are to increase biomass and sugar yield. We validated quantitative trait loci (QTLs) controlling plant height, biomass, juice weight and Brix with 181 recombinant inbred lines derived from a cross between Shihong137, a dwarf grain sorghum, and L-Tian, a tall sweet sorghum, under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…6 ; qPH7 and qPH9 ). Comparing these QTLs with those reported previously using the QTL Atlas 50 , both QC7 and QC9 were supported by numerous previous reports of plant height- and panicle length-related QTLs in sorghum 27 , 51 57 (Table S1 ). In sorghum, four major loci controlling plant height, Dw1 , Dw2 , Dw3 , and Dw4 , have been extensively characterized and reported that their recessive alleles reduce internode length 6 .…”
Section: Resultssupporting
confidence: 88%
“…6 ; qPH7 and qPH9 ). Comparing these QTLs with those reported previously using the QTL Atlas 50 , both QC7 and QC9 were supported by numerous previous reports of plant height- and panicle length-related QTLs in sorghum 27 , 51 57 (Table S1 ). In sorghum, four major loci controlling plant height, Dw1 , Dw2 , Dw3 , and Dw4 , have been extensively characterized and reported that their recessive alleles reduce internode length 6 .…”
Section: Resultssupporting
confidence: 88%
“…QTL clusters controlling PH, TB, STI‐TB, SFW and JW were consistently mapped in the marker interval of Xcup19‐SB4177 on chromosome 7 under salt stress condition (Figure ). In previous normal field condition, QTLs for PH, TB and SFW were always identified to have a positive effect from L‐Tian (Guan et al, ; Wang et al, ). Dw3 , a putative gene controlling PH in sorghum, was reported to be physically located at approximately 58,610,896–58,618,660 bp on chromosome 7 (Mace & Jordan, ) and was found only between Xcup19‐SB4177.…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypic values of PH, SD, TB, SFW, JW and Brix under normal and salt stress conditions in 2014 and 2016 were considered as replications utilized for statistical analysis using Minitab version 17.3.1 (Minitab). Linkage groups (LGs) were constructed using Mapmaker/EXP3.0 (Lincoln, Daly, & Lander, ) and detailed information for the RILs genetic map with 181 simple sequence repeats (SSR) was described in previous studies (Wang et al, , ). Phenotypes of PH, SD, TB, SFW, JW and Brix under salt stress conditions and STI‐PH, STI‐SD, STI‐TB, STI‐SFW, STI‐JW and STI‐Brix based on the pooled data in 2014 and 2016 were utilized to analyse QTLs using a composite interval mapping (CIM) module of Cartographer 2.5 (Wang, Basten, & Zeng, ).…”
Section: Methodsmentioning
confidence: 99%
“…For QTL confirmation, one scheme is to detect QTLs in early generations like F 2 and F 2:3 , and then confirmed in advanced generations from the same cross. Such approach have been successfully conducted in rice 9 , sweet sorghum 10 , soybean 11 , cucumber 12 . And the early generations with beneficial effect would be served as new breeding materials for cultivating new varieties 7 .…”
Section: Introductionmentioning
confidence: 99%